2015
DOI: 10.1007/s13592-015-0350-5
|View full text |Cite
|
Sign up to set email alerts
|

Orchid bees: a new assessment on the rarity of diploid males in populations of this group of Neotropical pollinators

Abstract: -The incidence of diploid males among 1457 individuals of different populations of six euglossine bee species (Eufriesea violacea , Eulaema cingulata , Euglossa annectans , Euglossa iopoecila , Euglossa pleosticta and Euglossa truncata ) was investigated with microsatellite markers. Bees were surveyed in Atlantic Forest fragments showing different sizes and degrees of human interference. Our analyses revealed that, although the frequencies of diploid males remained below 10 % for five out of six species studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Pearson & Dressler, 1985, Sofia et al, 2004Farias et al, 2007;Rocha-Filho & Garófalo, 2014). The distribution patterns of abundance in the sampled areas were similar to those of other studies made in other Atlantic Forest fragments; a few species had many individuals, and many species had few individuals (e.g., Rebêlo & Garófalo, 1997;Sofia & Suzuki, 2004;Sofia et al, 2004;Aguiar & Gaglianone, 2008;Ramalho et al, 2009;Giangarelli et al, 2015;Rocha-Filho & Garófalo, 2013). This tendency can be the result of the weak association of some species with the essences used (Viana et al, 2002) or can be the distribution pattern of these communities (Aguiar & Gaglianone, 2008).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Pearson & Dressler, 1985, Sofia et al, 2004Farias et al, 2007;Rocha-Filho & Garófalo, 2014). The distribution patterns of abundance in the sampled areas were similar to those of other studies made in other Atlantic Forest fragments; a few species had many individuals, and many species had few individuals (e.g., Rebêlo & Garófalo, 1997;Sofia & Suzuki, 2004;Sofia et al, 2004;Aguiar & Gaglianone, 2008;Ramalho et al, 2009;Giangarelli et al, 2015;Rocha-Filho & Garófalo, 2013). This tendency can be the result of the weak association of some species with the essences used (Viana et al, 2002) or can be the distribution pattern of these communities (Aguiar & Gaglianone, 2008).…”
Section: Discussionsupporting
confidence: 84%
“…As part of this rich biodiversity, Euglossine bees (Hymenoptera: Apidae: Euglossini), commonly known as orchid bees, have been widely sampled in different Neotropical ecosystems in recent decades, mostly in fragments or remnants of the Atlantic Forest (e.g. Rebêlo & Garófalo, 1997;Tonhasca et al, 2002;Sofia et al, 2004;Aguiar et al, 2014;Rocha-Filho & Garófalo, 2013Giangarelli et al, 2015;Costa & Francoy, 2017). Some these studies have shown structural differences in euglossine bee communities from distinct biogeographical regions, and differences have usually been attributed mainly to historical factors (Aguiar et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The amplification reactions were carried out at a final volume of 10 μl, containing 2.3 μl water, 1X GoTaq Colorless Master Mix (Promega, Fitchburg, WI, USA), 10 ng DNA sample, 1% glycerol, 0.125 μM M13 fluorescent labeled primer (FAM, HEX, NED, or PET; Applied Biosystems, Carlsbad, CA, USA), 0.125 μM reverse primer, and 0.0125 μM forward primer. Polymerase chain reactions were performed in a thermal cycler ProFlex 3 × 32‐well PCR System (Thermo Fisher Scientific, Waltham, MA, USA) programed as follows: initial denaturation at 94 °C for 5 min, followed by 10 cycles at 94 °C for 30 s, 48 °C, 54 °C, 58 °C, or 60 °C for 1 min, 72 °C for 1 min, 25 cycles at 89 °C for 30 s, 48 °C, 54 °C, 58 °C, or 60 °C for 1 min, 72 °C for 1 min, and the final extension at 72 °C for 30 min (Giangarelli et al., ). Electrophoresis of amplification products was performed in ABI PRISM 3500‐XL automated sequencer (Applied Biosystems), using the GeneScan 600 Liz (Applied Biosystems) molecular weight marker.…”
Section: Methodsmentioning
confidence: 99%
“…The AutoDimer software was used to check for specificity and possible primer dimer or hairpin loop (Vallone & Butler, 2004). The selected loci were tested under different amplification conditions and then underwent individual genotyping in an automatic sequencer, following the protocol described by Schuelke (2000) and Giangarelli et al (2015). To perform the reading in the automatic sequencer, fluorescent-labeling required an additional forward primer with an M13 universal sequence (5 0 -TGTAAAACGACGGCCAGT-3 0 ) added to the 5 0 end of each locus (Schuelke, 2000).…”
Section: Development and Characterization Of Eight Microsatellite Locimentioning
confidence: 99%